Answer :

In this question the following formulas will be used:


sin (A - B) = sinA cos B - cosA sinB


cos (A - B) = cosAcosB+ sinAsinB


=


=


=


=


=.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

In any triangle ARD Sharma - Mathematics

In any triangle ARD Sharma - Mathematics

In any triangle ARD Sharma - Mathematics

In any triangle ARD Sharma - Mathematics

In any triangle ARD Sharma - Mathematics

In any triangle ARD Sharma - Mathematics

In any triangle ARD Sharma - Mathematics

In any triangle ARD Sharma - Mathematics

<span lang="EN-USRD Sharma - Mathematics

In any ∆ABC, if aRD Sharma - Mathematics